Effect of World Commodity Prices on the Movement of the FTSE Index on The Indonesia Stock Exchange 2020-2023 - Vivin Hanitha; Tri Angreni; Hendra Hendra (Komunitas Dosen Indonesia, 2024)
This research aims to analyze the relationship between commodity prices (gold, gas, tin, silver, nickel, oil) and the FTSE Indonesia stock market index. This research uses secondary data for the research period from January 2020 to December 2023. The analytical method used in this research is the multiple linear regression analysis method. Linear regression analysis is used to test the influence of commodity prices on changes in the value of FTSE Indonesia. The results of this research show that the gas, tin, silver and nickel index variables have a negative effect on the FTSE Index. The Oil, Nike, Gas and Tin variables have a positive influence while the Gold and Silver variables do not have a negative influence, indicating that they do not have a significant influence on the FTSE Index. The results of the analysis show that the overall regression model has a significant fit to the data, with an R-squared value of 75.58% of the variation in FTSE Indonesia can be explained by the commodity price variables included in the model. The rest are factors outside the commodity variable. In addition, the significant F-statistic (21.15427) with a low p-value 0.00 indicates that the overall regression model is very significant. These findings show that commodity prices, including gold, gas, tin, silver, nickel and oil, together have a significant influence on the movement of FTSE Indonesia. The implications of this research can help investors and decision makers to understand the dynamics of stock and commodity markets, as well as estimate the impact of changes in commodity prices on stock market performance in Indonesia.